Peningkatan kemampuan komunikasi matematik peserta didik melalui model Learning Cycle 5E (LC) dengan pendekatan scientific - Mida Tsamrotul Hamidah; Ipah Muzdalipah (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
The aim of this research is to know the improvement of students’ mathematical communication ability which the better one between the learning with scientific approach by way of the Learning Cycle 5E (LC) model with by way of the Discovery Learning model and knowing the mathematical disposition of the students by way of the LC model with Scientific approach. This research is in the form of quantitative research with  used experiment methode research. The population in this research is all students of class X Accounting SMK Sukapura Tasikmalaya Regency. The samples were taken by two random sampling. The data collection technique performs the test of mathematical communication ability and disseminates the student’s mathematical disposition questionnaire. The research of instrument used is the test of mathematical communication ability and questionnaire of students’ mathematical disposition. Analysis techniques of data is used the test of hypothesis that test the difference of two average with a significance level of 1%. Based on the results of research, processing, data analysis and hypothesis testing obtained by the conclusion that: Improvement of students’ mathematical communication ability with scientific approach by way of the LC model is better than by way of the Discovery Learning model. Student’s mathematical disposition by way of the LC model with scientific approach is in high category.Keywords:Mathematical Communication Skills, Mathematical Disposition, Learning Cycle 5E (LC) Model, Scientific Approach.